2018
DOI: 10.1002/chem.201705340
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Synthesis of Peptoid Macrocycles

Abstract: Over the past two decades, developing medical applications for peptides has, and continues to be a highly active area of research. At present there are over 60 peptide‐based drugs on the market and more than 140 in various stages of clinical trials. The interest in peptide‐based therapeutics arises from their biocompatibility and their ability to form defined secondary and tertiary structures, resulting in a high selectivity for complex targets. However, there are significant challenges associated with the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 110 publications
0
52
0
Order By: Relevance
“…The ether side chain, like in the Nte monomers, has been shown in previous peptoid studies to exhibit antifouling and surface passivation properties. That can prevent surface adsorption of biomolecules in physiological environments and inhibit enzymatic degradation of DNA origamis due to proteases and nucleases (44,46,53,54).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ether side chain, like in the Nte monomers, has been shown in previous peptoid studies to exhibit antifouling and surface passivation properties. That can prevent surface adsorption of biomolecules in physiological environments and inhibit enzymatic degradation of DNA origamis due to proteases and nucleases (44,46,53,54).…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we demonstrate that peptoid-based coating provides a tunable platform for protecting DNA nanostructures in a broad range of bioactive environments. Peptoids, comprising N-substituted glycines, are an emerging class of peptidomimetic molecules that offer biocompatibility, low-cost synthesis, high chemical flexibility, and designable sequences and performances (42)(43)(44). In a recent study, Xuan et al (45) demonstrated that peptoid architectures could be engineered at the atomic level, resulting in a variety of atomically defined structural arrangements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A, Different strategies for the improvement of peptide stability to proteolytic cleavage. The images are schematic representations of molecules constructed by: d amino‐acids (empty circles); unnatural amino‐acids (full squares and pentagons); cyclization through the use of disulfide bonds obtained by cysteines oxidation (black circles); structural constraints given by the presence of amino‐acids like, for example, proline or histidine (curved line on full circles); peptidomimetics, where for example, the nitrogen atom of the amide backbone is used rather than the α‐carbon as in the case of peptides (thick ribbon); branched peptides where two or four identical peptides are linked together by an amino acidic core (empty squares). B, Schematic representation of nanocarriers used to link drugs, including peptides, for the improvement of bioavailability.…”
Section: General Properties Of Branched Peptidesmentioning
confidence: 99%
“…Therefore, we report here an innovative and facile method to carry out symmetrical tetra modifications around the DOTA scaffold using the unique active site distribution patterns of commercially available resins. We once again chose peptoids as our main source of modifying moieties due to the facile and straightforward chemistry involved with peptoid synthesis …”
Section: Introductionmentioning
confidence: 99%